Determination of reliable fatigue life predictors for magnetorheological elastomers under dynamic equi-biaxial loading. (August 2017) - Zhou, Yanfen; Jiang, Liang; Chen, Shaojuan; Ma, Jianwei; Betts, Anthony; Jerrams, Stephen
Abstract: Fatigue life prediction is of great significance in ensuring magnetorheological elastomer (MRE) based rubber components exhibit reliability and do not compromise safety under complex loading, and this necessitates the development of plausible fatigue life predictors for MREs. In this research, silicone rubber based MREs were fabricated by incorporating soft carbonyl iron magnetic particles. Equi-biaxial fatigue behaviour of the fabricated MREs was investigated by using the bubble inflation method. The relationship between fatigue life and maximum engineering stress, maximum strain and strain energy density were studied. The results showed that maximum engineering stress and stored energy density can be used as reliable fatigue life predictors for SR based MREs when they are subjected to dynamic equi-biaxial loading. General equations based on maximum engineering stress and strain energy density were developed for fatigue life prediction of MREs.